Entrepreneurship Assistance for Indonesian Workers Retirement Program BNP2TKI Ringinrejo District, Kediri Regency - Purtiningtyas, Lilis; Sutisna, Sutisna; Komarudin, Mamay; Kusuma, Jaka Wijaya; Hamidah, Hamidah (Yayasan Education and Social Center, 2024)
The entrepreneurship mentoring program for retired Indonesian Workers (TKI) in Ringinrejo District, Kediri Regency, is designed to empower participants returning from abroad to adapt and develop economic independence. Through a holistic approach, the program includes socialization, entrepreneurial skills training, mentoring, and access to financing sources. The results of the implementation showed that participants successfully prepared a business plan and started a business, both in the culinary sector and other businesses, based on their experience and skills. Interaction between participants forms a social network that supports, strengthens confidence, and creates a collaborative environment. Additionally, participant involvement in the program evaluation process provides valuable insights for continuous improvement. The positive impact of this program is not only seen in improving the skills of individual entrepreneurs, but also in the creation of jobs and strengthening the local economy. With steps forward that include broader product marketing and good financial management, it is hoped that this success can be sustainable and become an inspiration for the next generation of retired migrant workers